FEASIBILITY OF STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATEMATHICS)-BASED STUDENT WORKSHEET IN ENERGY SUB-MATERIAL TO IMPROVE CRITICAL THINKING SKILLS - Riska Yulianah; An Nuril Maulida Fauziah (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This study aims to describe the validity, practicality, and effectiveness of STEM-based student worksheets to improve critical thinking. The research method using the ADDIE development model include Analyze, Design, Development, Implement, and Evaluation stages. Research design uses One Group Pretest-Postest. Research subjects were 33 students of VII-L class at Junior High School 21 Surabaya. Pretest and posttest analyzed using N-gain scores. The results obtained are the validity of student worksheets get score 5 with very valid criteria. Practicality Student worksheets in implementation of PjBL-STEM learning overall get score 5 with very well criteria, and the highest percentage of 24.30% in designing, making, and simple project experiments Wind -Up Car. The effectiveness of student worksheets in pretest results get average of 41.09 and the posttest results get average of 73.51 with average N-gain score of 0.56 (medium category). The percentage of N-gain with high category was 24.24% and the medium category was 75.76%. Students' critical thinking skills have increased in each indicator, the highest increase in Advanced clarification is 50.76%, Elementary clarification is 22.28%, Basic support is 1.36%, Inference is 45.15%, and Strategies and tactics is 40.15%. The average results of responses to student worksheets obtained 88.49% with a very well category. The conclusion of the study is STEM-based student worksheets are declared feasible to improve critical thinking skills. STEM student worksheets that implemented with the suitable learning model become one of the learning alternatives to support the activeness of students and improve critical thinking skills.